POLITICS OF MEMORY IN ACTIVITY OF POLISH POLITICAL PARTIES - Федорищак, Х. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article disclosed the essence and specific policy terms of memory and historical memory. The concept of politics of memory during the last decades did a swift career, becoming one of the most substantial themes of public discussions. A national revival and disintegration of the communist-socialistic system in Europe resulted in appearance of the numerous political forming activity of that assisted claim of interpretation of the past and forming of civil society. Political parties from the moment of their origin become one of main subjects of nation-building and of state-building. Exactly parties articulate the values of national association at political level, formulate national interests and incarnate them in life. Analyzed election programs, resolutions, laws and activities of Prawo i Sprawiedliwość, Platforma Obywatelska, Ruch Palikota, Kukiz’15, Nowoczesna, Polskie Stronnictwo Ludowe, Sójusz Lewicy Demokratycznej, Unia Pracy the major political parties from 1989 to 2016 rr. From the beginning of the work political parties called to distribute patriotism and strengthen public and national solidarity of Poland. In their opinion, the Polish people that comes forward as basis of the state must stand in the center of the political thinking. Most political parties determined a culture the source ofidentity of nation, mortgage of development, and basis of understanding with the past. However in practice activity of parties in area of historical politics often generated misunderstanding as in the middle of the state so as between nearby countries. For example, Left political forces consistently rejected all attempts decommunisation and lustration and the national conservative, the radically adjusted forces accused of events on Volyn in 1943 only the Ukrainian nationalists, in particular OUN-UPA.